Anaeramoeba pumila sp. nov. and Anaeramoeba sp. OCE22C represent two novel types of symbiosis of Anaeramoebae and prokaryotes - Pavlátová, Magdaléna; Hanousková, Pavla; Čepička, Ivan (The Journal of eukaryotic microbiology, 2024)
Anaeramoebae is a recently described phylum of anaerobic, marine amoebae, and amoeboflagellates belonging to the Metamonada supergroup. So far, six species have been described based on light microscopic morphology and sequences of the SSU rRNA gene. Here we present three new strains of Anaeramoeba with a description of their morphology, ultrastructure, and phylogenetic position based on the analysis of SSU rRNA gene sequences. Two of the strains represent a new species, Anaeramoeba pumila sp. nov., that has the smallest cells of all known Anaeramoeba species, and one that represents a species from the newly recognized Anaeramoeba flamelloides complex. Anaeramoebae are known to have a syntrophic relationship with prokaryotes. Our strains display two novel, remarkable types of symbioses, previously unknown from Anaeramoebae.
Keywords: Phylogeny; RNA, Ribosomal, 16S; ultrastructure; Amoeba; morphology; mikroskopie; Sequence Analysis, DNA; Symbiosis; RNA ribozomální 16S; marine; phylogeny; new taxa; Eukaryota; symbióza; sekvenční analýza DNA; Microscopy; fylogeneze; anaerobiosis; SSU rRNA gene